GEOGRAPHIC INFORMATION SYSTEM-BASED ASSESSMENT OF ENVIRONMENTAL CHALLENGES AND GREEN INFRASTRUCTURE PLANNING IN THE TALLO RIVER WATERSHED, MAKASSAR CITY - Poppy Indrayani; Ibrahim Djamaluddin; Ritnawati Ritnawati; Anugrah Anugrah; Darwis Baso; Mursyid Hasnawi; Miftahul Khaer; Asmeati Asmeati; Hiroyuki Honda; Rastina Kalla; Ahmed M Meneisy (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2025)
Aims: This study aims to explore the key issues and potential for implementing Green Infrastructure (GI) in the Tallo River area of Makassar, the largest city in Eastern Indonesia. Given its strategic location near the city center and its extensive undeveloped wetlands, the Tallo River region presents a valuable opportunity for sustainable urban development. The research emphasizes the need for integrated planning that addresses natural, economic, and social dimensions, positioning the Tallo River as a multifunctional resource capable of delivering diverse environmental benefits. Methodology and results: Using Geographic Information Systems (GIS) as a decision support and spatial analysis tool, this study evaluates environmental and socio-economic characteristics of the Tallo River area within the Green Infrastructure framework. Spatial data were analyzed to identify and map existing ecological functions, climate adaptation potential, and flood mitigation capacities. Through this process, various GI components and their functions were classified, and priority zones for Green Infrastructure implementation were delineated based on overlapping environmental and social values. Conclusion, significance and impact study: The findings highlight the critical role of GIS in supporting integrated urban planning and environmental management. Conceptualizing the Tallo River area as a multifunctional green space offers a pathway to enhance ecological resilience, address climate risks, and improve urban livability. This study provides actionable insights for policymakers and urban planners, reinforcing the significance of spatial analysis in guiding sustainable development strategies in rapidly urbanizing regions.